Frequency/Magnitude Analysis of Wave Events at Duck, North Carolina - Hill, Stephanie (East Carolina University, 2010)
There is a great need for predicting shoreline and beach change due to storms. Firstly, shoreline erosion rates along the East Coast are as high as 70%. And more importantly, people live along the coast. Between 1980-2003 33 million people moved to the coast. Previous research includes looking at successive before and after storm profiles and the application of the partial duration approach for classifying storms events. Storm scales and indicators are widely created but most are qualitative in nature, therefore making them not useful for predicting future events.    Frequency/magnitude in geomorphology quantifies events and puts them into context with regards to integrated landscape change. Past research has concluded that events of moderate frequency/magnitude transport the most sediment along a beach profile. Wave data from the USACE Field Research Facility (FRF) at Duck, North Carolina are used to perform a partial duration series analysis for determining wave events. The standard energy equation along with a duration component is used to quantify event magnitude and the total event energy is standardized into a storm index, based 0-10. Profile data was acquired to determine the beach change associated with these wave events.   It was found that events of low magnitude produced the most change on the beach. There was a great amount of volumetric variability between the profiles suggesting the need to incorporate wave angle to account for alongshore transport of sediment. There is also a need to extend profiles past the 8m depth to fully account for total volumetric change.
Keywords: Physical geography; Beach erosion--North Carolina--Duck; Beaches--North Carolina--Duck; Shorelines--North Carolina--Duck; Sediment transport--North Carolina--Duck; Ocean waves--North Carolina--Duck; Storms--North Carolina--Duck